1990
DOI: 10.1042/bj2690239
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic role of single residues within the main immunogenic region of the nicotinic acetylcholine receptor

Abstract: The target of most of the autoantibodies against the acetylcholine receptor (AChR) in myasthenic sera is the main immunogenic region (MIR) on the extracellular side of the AChR alpha-subunit. Binding of anti-MIR monoclonal antibodies (mAbs) has been recently localized between residues alpha 67 and alpha 76 of Torpedo californica electric organ (WNPADYGGIK) and human muscle (WNPDDYGGVK) AChR. In order to evaluate the contribution of each residue to the antigenicity of the MIR, we synthesized peptides correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
6

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 33 publications
0
25
1
6
Order By: Relevance
“…Although anti-MIR antibodies bind with high affinity to the intact AChR, they bind with low afinity to the synthetic MIR peptides. However, it was noticed both in earlier studies (Papadouli et al, 1990;Bellone et al, 1989) and in the present work that some analogues, especially of a73 and a76, often enhanced binding of the tested anti-MIR mAbs. Subsequent study of selected single and double substitutions on a73 and a76 showed that some of these substitutions had a dramatically enhanced mAb binding activity (Fig.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Although anti-MIR antibodies bind with high affinity to the intact AChR, they bind with low afinity to the synthetic MIR peptides. However, it was noticed both in earlier studies (Papadouli et al, 1990;Bellone et al, 1989) and in the present work that some analogues, especially of a73 and a76, often enhanced binding of the tested anti-MIR mAbs. Subsequent study of selected single and double substitutions on a73 and a76 showed that some of these substitutions had a dramatically enhanced mAb binding activity (Fig.…”
Section: Discussioncontrasting
confidence: 44%
“…However, the binding efficiency of anti-MIR mAbs to a67-76 peptides, as well as to any denatured AChR fragment, is very low in comparison to that of the intact AChR. A~~~~ the above-studied ~1~ substitutions, those on a73 and a76 appeared to enhance anti-MIR mAb binding (Papadouli et al, 1990). Further study ofthe enhancemerit effect towards the design of an MIR peptide with antigenicity to that of the MIR on the intact AChR, would have potential clinical applications.…”
Section: Synthetic Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding of several anti-MIR monoclonal antibodies (mAb) has been localised within residues 67-76 of the a-subunit [7]. The antigenic role of each residue within a67-76 has been examined and it has been shown that residues a68-71 are [I 115231 the most critical [8,91. The conformation of the a67-76 peptide, either free or bound on an anti-MIR mAb, has been elucidated by two-dimensional nuclear magnetic resonance (NMR) studies [lo, 111.…”
Section: Introductionmentioning
confidence: 99%